2011
DOI: 10.1128/jcm.00940-11
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex 5′ Nuclease-Quantitative PCR for Diagnosis of Relapsing Fever in a Large Tanzanian Cohort

Abstract: Relapsing fever (RF) is caused by tick-and louse-borne Borrelia spp., is characterized by recurrent fever, and is often misdiagnosed as malaria. Because of submicroscopic bacteremia, microscopy can be insensitive between febrile bouts. We designed a multiplex quantitative PCR (qPCR) assay to distinguish RF Borrelia from Plasmodium falciparum and P. vivax. The assay specifically (100%) amplified pathogenic RF Borrelia (1 copy/reaction). We then tested blood from participants within a Tanzanian cohort assessed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Also, the multiplex real-time PCR proved highly sensitive, detecting 100 copies, that is more sensitive than the 10 3 –10 5 borreliae/µL reported for microscopy [14], [24]. Previously, borreliae not detectable by microscopy, were detected by using real-time PCR targeting the fla and the glpQ genes [3], [15]. These assays however could not identify borreliae at the species level [3], [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the multiplex real-time PCR proved highly sensitive, detecting 100 copies, that is more sensitive than the 10 3 –10 5 borreliae/µL reported for microscopy [14], [24]. Previously, borreliae not detectable by microscopy, were detected by using real-time PCR targeting the fla and the glpQ genes [3], [15]. These assays however could not identify borreliae at the species level [3], [15].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, real-time PCR targeting the 16S rRNA gene or the glpQ gene improved the sensitivity of the diagnosis when compared to microscopy [14], [15]. Also, we previously showed that PCR-sequencing intergenic spacers could be used for genotyping B. crocidurae , B. duttonii and B. recurrentis [16].…”
Section: Introductionmentioning
confidence: 99%
“…In order to estimate the true concentration of pathogen DNA available in whole blood for molecular analysis from patients with bloodstream infections, we analyzed the data available in the literature. Organism-specific quantitative PCR has been used to measure the bacterial DNA present in whole-blood specimens from patients with sepsis, pneumonia, or suspected bloodstream infections (13,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Each of these studies analyzed whole-blood specimens from patients with suspected or confirmed infections rather than spiked samples for which the genome-to-viable cell ratio is expected to be close to 1:1.…”
Section: Repeated Analytical Testing By Pcr/esi-msmentioning
confidence: 99%
“…Several studies have assessed the effect of fastidious bacterial infections in systemic febrile illness, including Rickettsia felis ( 4 6 ), Coxiella burnetii ( 7 ), Tropheryma whipplei ( 3 ), and Borrelia spp. ( 1 , 8 ). Tourism, immigration, international business travel, international aid work, and the deployment of troops overseas were documented as contributors to a tremendous increase in international travel during 1996–2004 ( 9 ).…”
mentioning
confidence: 99%